Who Fills the Void When the United States Turns Away from Global Science? - Glass, Chris; de Wit, Hans; Altbach, Philip (International Higher Education, 2025)
<h3 id="the-united-states-is-surrendering-its-advantage-in-global-science-not-through-defeat-but-deliberate-withdrawal-as-visa-revocations-mount-and-research-budgets-collapse-international-talent-is-fleeing-this-self-inflicted-isolationism-creates-a-vacuum-precisely-when-global-collaboration-on-climate-pandemics-and-artificial-intelligence-is-most-critical-the-question-is-not-whether-the-world-will-adapt-but-how-quicklyand-at-what-cost" data-pm-slice="1 1 []">The United States is surrendering its advantage in global science, not through defeat but deliberate withdrawal. As visa revocations mount and research budgets collapse, international talent is fleeing. This self-inflicted isolationism creates a vacuum precisely when global collaboration on climate, pandemics, and artificial intelligence is most critical. The question is not whether the world will adapt, but how quickly—and at what cost.